THE IMPACT OF TELEVISION COSMETICS ADVERTISEMENT ON WOMEN PURCHASING HABITS: A CASE STUDY OF NAROWAL - Dr Muhammad Kamran Khan; Ayesha Arshad; Zunaira Islam (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of the study is to examine the impact of television cosmetics advertising on women purchasing habits (A case study of Narowal). The primary objective of the study was to investigate the effects of television cosmetics advertisement on the life patterns of women in Narowal, Pakistan. The attitude towards advertising has been changing rapidly at any time with diversification and dynamism. Researcher used cultivation and usage and Gratification theory as theoretical frame to support the phenomena. Researcher used Survey method to collect the response about The Impact of Television cosmetics advertisement in women purchasing hobbits. Sample size is taken 200 from Distinct Narowal; 100 from Master level and 100 from BS level. Also respondents pay attention on celebrity style and the theme of advertisements. Meanwhile most of the women watching advertisement through the internet, women’s purchasing decision depend on attractive look of product after expose to advertisement, Most of women purchased fair& Lovely product after coming across the advertisement. Somewhat, women’s use the cosmetics after watching the television advertisement. Result reflects that the impacts of Television cosmetics advertisements are overstated than reality.